Jaringan Sensor Nirkabel Multisensor untuk Pemantauan Aktivitas Gunung Api dan Peringatan Dini Berbasis IoT - Raihan Qodri; Melany Febrina; Eko Satria (Jurnal Fisika Unand, 2026)
This research presents the development of a multisensor wireless monitoring system designed to observe ground vibration, CO₂ concentration, and SO₂ concentration as early indicators of volcanic activity. The system integrates an ADXL335 accelerometer, MG-811 CO₂ sensor, and MQ-136 SO₂ sensor with an Arduino-based microcontroller, LoRa communication modules, and an Internet-of-Things (IoT) platform for real-time monitoring. Sensor calibration was carried out using controlled laboratory procedures, including drop tests for vibration measurement and gas exposure tests for CO₂ and SO₂ detection. The IoT layer, consisting of an MQTT-based web dashboard and automated Telegram notifications, successfully visualized sensor data and delivered early-warning messages during the outdoor test. The three-day outdoor simulation demonstrated stable operation of the sensor nodes, LoRa transmission, and solar-powered supply. Although the system has not yet been validated in a real volcanic environment, the prototype shows the feasibility of integrating multiple sensing modalities with low-power wireless communication and IoT-based data services. This indicates its potential for further development into a field-deployable volcanic monitoring and early-warning system.